CSK-mediated signalling by integrins in cancer - Maldonado, Horacio; Leyton, Lisette (Frontiers in Cell and Developmental Biology, 2023)
Cancer progression and metastasis are processes heavily controlled by the integrin receptor family. Integrins are cell adhesion molecules that constitute the central components of mechanosensing complexes called focal adhesions, which connect the extracellular environment with the cell interior. Focal adhesions act as key players in cancer progression by regulating biological processes, such as cell migration, invasion, proliferation, and survival. Src family kinases (SFKs) can interplay with integrins and their downstream effectors. SFKs also integrate extracellular cues sensed by integrins and growth factor receptors (GFR), transducing them to coordinate metastasis and cell survival in cancer. The non-receptor tyrosine kinase CSK is a well-known SFK member that suppresses SFK activity by phosphorylating its specific negative regulatory loop (C-terminal Y527 residue). Consequently, CSK may play a pivotal role in tumour progression and suppression by inhibiting SFK oncogenic effects in several cancer types. Remarkably, CSK can localise near focal adhesions when SFKs are activated and even interact with focal adhesion components, such as phosphorylated FAK and Paxillin, among others, suggesting that CSK may regulate focal adhesion dynamics and structure. Even though SFK oncogenic signalling has been extensively described before, the specific role of CSK and its crosstalk with integrins in cancer progression, for example in mechanosensing, remain veiled. Here, we review how CSK, by regulating SFKs, can regulate integrin signalling, and focus on recent discoveries of mechanotransduction. We additionally examine the cross talk of integrins and GFR as well as the membrane availability of these receptors in cancer. We also explore new pharmaceutical approaches to these signalling pathways and analyse them as future therapeutic targets.